2022
DOI: 10.1111/mec.16698
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding suggests adaptive seasonal variation of individual trophic traits in a critically endangered fish

Abstract: Dietary studies are critical for understanding foraging strategies and have important applications in conservation and habitat management. We applied a robust metabarcoding protocol to characterize the diet of the critically endangered freshwater fish Zingel asper (the Rhone streber). We conducted modelling and simulation analyses to identify and characterize some of the drivers of individual trophic trait variation in this species. We found that population density and ontogeny had minor effects on the trophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 237 publications
(287 reference statements)
0
6
0
Order By: Relevance
“…Apart from finding adequate parameters for data analyses, mock samples are also useful in ensuring that sufficient sequencing coverage has been achieved. Furthermore, in large-scale studies involving several distinct high-throughput sequencing runs, the systematic use of identical mock samples as standards for parametrization of the filtering should minimize the effect of random fluctuations and make samples comparable between runs [12] , [40] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from finding adequate parameters for data analyses, mock samples are also useful in ensuring that sufficient sequencing coverage has been achieved. Furthermore, in large-scale studies involving several distinct high-throughput sequencing runs, the systematic use of identical mock samples as standards for parametrization of the filtering should minimize the effect of random fluctuations and make samples comparable between runs [12] , [40] .…”
Section: Discussionmentioning
confidence: 99%
“…While the stringent filtering of VTAM decreases (within-sample) α-diversity and increases (between-samples) β-diversity, it has proven to provide accurate estimates to conduct robust ecological studies (e.g. [40] ). We, therefore, believe VTAM represents an innovative and so-expected tool for the robust validation of metabarcoding data and for conducting ecological analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study modeled the distribution of two co-occurring benthic catshark species to investigate intra-and interspecific spatial associations between coasts, maturity stages, and across depth ranges. Numerous studies have reported that ecologically and morphologically similar species may facilitate successful co-existence through partitioning their ecological niches (Holmgren, 1995;Pilfold et al, 2014;Villsen et al, 2022;Weideli et al, 2023). This appears to be the case in the present study, with catsharks displaying differential habitat occupancy, specifically intra-and interspecific differences in co-occurrence patterns and spatial associations between coasts, maturity stages, and across the depth ranges explored.…”
Section: Discussionmentioning
confidence: 99%